Limnological parameters in Sôya Coats lakes between the 55th and 56th Japanese Antarctic Research Expeditions in 2014–2015 —Long-term monitoring study— - KUDOH, Sakae; TAKAHASHI, Kunio T.; ISHIHARA, Tomoko; TSUJIMOTO, Megumu; NAKAI, Ryosuke; SUZUKI, Atsushi C.; TANABE, Yukiko; UCHIDA, Masaki; IMURA, Satoshi (2016)
Fig. 1, 2 | http://polaris.nipr.ac.jp/~parc/pub/v004/nipr_parc_362_0023.docx departmental bulletin paper